Association between metabolic score for visceral fat and chronic pain: a cross-sectional analysis of NHANES 1999–2004 - Zhu, Jianyu; Wang, Yixuan; Yu, Guangchao; Li, Lin; He, Jinyong; Liao, Huilian; Wu, Xianping (Frontiers in Nutrition, 2025)
BackgroundThe Metabolic Score for Visceral Fat (METS-VF) offers a refined measure of visceral adiposity, potentially surpassing traditional metrics. This study examines the association between METS-VF and chronic pain in U.S. adults.MethodsWe analyzed data from 5,905 adults aged 18 years and older from the National Health and Nutrition Examination Survey (NHANES) 1999–2004. Weighted multivariate linear regression and restricted cubic spline analyses were conducted to investigate the linear associations between METS-VF and chronic pain. Threshold effects were determined using a two-part linear regression model. Subgroup analyses were conducted across three age groups (18–39, 40–64, and ≥65 years). The predictive accuracy of METS-VF, body mass index (BMI), and waist circumference (WC) was evaluated using ROC curve analysis. Influential predictors of chronic pain were identified via XGBoost, and mediation analysis assessed the role of C-reactive protein (CRP).ResultsAmong participants (mean age, 46.8 years; 50.8% female), chronic pain prevalence was 14.6%. Higher METS-VF was associated with increased odds of chronic pain (adjusted OR per unit increase, 1.46; 95% CI, 1.13–1.87), with a threshold effect at METS-VF 5.714. The highest METS-VF quartile showed greater odds of chronic pain (OR, 1.87; 95% CI, 1.28–2.72; P for trend = 0.003). In adults ≥65 years, METS-VF demonstrated superior discrimination (AUC, 0.618) compared to BMI and waist circumference. XGBoost identified METS-VF as the most influential predictor, with CRP partially mediating the association (7.4% of total effect; p = 0.01).ConclusionMETS-VF independently associated with higher odds of chronic pain, especially in older adults.